Fishing as a cybercrime in the Internet banking system: economic and legal aspects - Ilchenko, O. V.; Ільченко, О. В.; Chumak, V. V.; Чумак, В. В.; ORCID: http://orcid.org/0000-0002-6171-2250; Kuzmenko, S.; Shelukhin, O.; Dobrovinskyi, A. V.; Добровінський, А. В. (Journal of Legal, Ethical and Regulatory Issues. – 2019. – Vol. 22, Issue Special Issue 2, 2019)
У статті описано поняття фішингу як одного з видів кіберзлочинності у сфері Інтернет-шахрайства. Автори визначають особливості фішингу та його основне призначення. Досліджуючи суть фішингу як кіберзлочинності, звертали увагу на основні методи його реалізації. Було визначено нормативно-правову базу, щодо якої здійснюється міжнародне регулювання та протидія негативним явищам кіберзлочинності, включаючи фішинг. Особлива увага приділяється проблемі визначення відповідальності за вчинення кіберзлочинів, серед яких фішинг не є винятком, на рівні законодавства в різних країнах світу. Були закріплені значні перешкоди на шляху повного впровадження Інтернет-банкінгу. Встановлено важливість протидії шахрайству в системі економічної безпеки банку, включаючи фішинг.

The paper describes the concept of phishing as one of the types of cybercrime in the field of Internet fraud. The author identifies the features of phishing and its main purpose. When investigating the essence of phishing as a cybercrime, attention was paid to the main metho ds of its implementation. The legal and regulatory framework was determined, in relation ot which international regulation and counteraction to negative phenomena of cybercrime, including phishing, is carried out. Particular attention is paid to the issue of determination of responsibility for commitment of cybercrimes, among which phishing is not an exception, at the legislation level in different countries of world. Significant obstacles in the field of full implementation of Internet banking were charact erized. The importance of counteracting fraud in the system of economic safety of the bank, including phishing, was established.

В статье описано понятие фишинга как одного из видов киберпреступности в сфере Интернет-мошенничества. Авторы определяют особенности фишинга и его основное назначение. Исследуя суть фишинга как киберпреступности, обращали внимание на основные методы его реализации. Было определено нормативно-правовую базу, по которой осуществляется международное регулирование и противодействие негативным явлениям киберпреступности, включая фишинг. Особое внимание уделяется проблеме определения ответственности за совершение киберпреступлений, среди которых фишинг не является исключением, на уровне законодательства в разных странах мира. Были закреплены значительные препятствия на пути полного внедрения Интернет-банкинга. Установлено важность противодействия мошенничеству в системе экономической безопасности банка, включая фишинг.
Fishing as a cybercrime in the Internet banking system: economic and legal aspects / Oleksandr Ilchenko, Volodymyr Chumak, Serhii Kuzmenko and oth. // Journal of Legal, Ethical and Regulatory Issues. – 2019. – Vol. 22, Issue Special Issue 2. – 6 p.
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; publikatsii u zarubizhnomu vydanni; publikatsii u Scopus; cybercrime; кіберзлочинність; киберпреступность; phishing; фишинг; фішинг; cyberspace; кіберпростір; киберпространство; internet banking; Інтернет-банкінг; Интернет-банкинг